Petroleum related rock mechanics - Fjaer, Erling (Developments in petroleum science ;, 2008)
Engineers and geologists in the petroleum industry will find Petroleum Related Rock Mechanics, 2E, a powerful resource in providing a basis of rock mechanical knowledge - a knowledge which can greatly assist in the understanding of field behavior, design of test programs and the design of field operations. Not only does this text give an introduction to applications of rock mechanics within the petroleum industry, it has a strong focus on basics, drilling, production and reservoir engineering. Assessment of rock mechanical parameters is covered in depth, as is acoustic wave propagation in rock.